Prader–Willi syndrome can be diagnosed prenatally. (22nd October 2014) - Gross, Noa; Rabinowitz, Ron; Gross‐Tsur, Varda; Hirsch, Harry J.; Eldar‐Geva, Talia
<x xml:space="preserve">Abstract</x> The aim of this study was to characterize the fetal phenotype of a cohort of individuals with confirmed diagnoses of Prader‐Willi syndrome (PWS), a severe multi‐system genetic disorder, diagnosed by a specific methylation test. We interviewed mothers of 106 individuals with PWS to obtain information about the pregnancy of their affected child. For 47 pregnancies of children younger than 10 years, we also reviewed the obstetric ultrasound and detailed obstetric history from medical records. We compared the PWS pregnancies with those of the sibling closest in age and with the general population. McNemars, Chi‐square and Fisher exact tests were used for statistical analyses. Decreased fetal movements, small for gestational age (SGA), asymmetrical intrauterine growth (increased head/abdomen circumferences ratio) and polyhydramnios were found in 88%, 65%, 43%, and 34%, respectively (P < 0.001 vs. siblings and P < 0.0001 vs. the general population for all measurements). No severe morphological abnormalities were found. A combination of 2, 3, and 4 abnormalities was found in 27%, 29%, and 24% of pregnancies, respectively. Fourteen out of 15 umbilical artery Doppler studies were within the normal range (93%). The rare combination of asymmetrical intrauterine growth and polyhydramnios was found in 34% of PWS pregnancies (P < 0.0001 vs. the general population). Prenatal genetic screening for PWS by methylation testing is indicated when any combination of polyhydramnios, SGA or asymmetric intrauterine growth, with normal Doppler studies is present, particularly when asymmetrical intrauterine growth and polyhydramnios coexist. © 2014 Wiley Periodicals, Inc.